100 W - pump limited Yb3+ doped silica fiber laser - Franczyk, Marcin; Pysz, Dariusz; Buczyński, Ryszard (Photonics Letters of Poland, 2024)
We present the laser system based on developed in-house Yb3+ doped silica fiber with a large core with a diameter of 21 µm, dedicated to high power applications. In the laser system, we achieved a maximum output power of 107 W limited by the available pump diode, in 25 m long fiber with high slope efficiency of 65 %. The laser generated at wavelength of 1080 nm and with beam quality of Mx2 = 1.43 and My2 = 1.44. Full Text: PDF References I. Divliansky, High power fiber lasers (Institution of Engineering and Technology, 2019). DirectLink B. Yang, P. Wang, H. Zhang, X. Xi, C. Shi, X. Wang, and X. Xu, "6 kW single mode monolithic fiber laser enabled by effective mitigation of the transverse mode instability", Opt. Express 29, 26366 (2021). CrossRef IPG Photonics DirectLink J. Dawson, M. Messerly, R. Beach, M. Shverdin, E. Stappaerts, A. Sridharan, P. Pax, J. Heebner, C. Siders, C. Barty, "Analysis of the scalability of diffraction-limited fiber lasers and amplifiers to high average power", Opt. Expr. 16, 13240 (2008). CrossRef C. Jauregui, C. Stihler, and J. Limpert, "Transverse mode instability", Adv. Opt. Photon. 12, 429 (2020), CrossRef R. Krämer, F. Möller, C. Matzdorf, T. Goebel, M. Strecker, M. Heck, D. Richter, M. Plötner, T. Schreiber, A. Tünnermann, and S. Nolte, "Extremely robust femtosecond written fiber Bragg gratings for an ytterbium-doped fiber oscillator with 5 kW output power", Opt. Lett. 45, 1447 (2020). CrossRef M. Franczyk, D. Pysz, F. Włodarczyk, I. Kujawa, and R. Buczyński, "Yb3+ doped single-mode silica fibre laser system for high peak power applications", Phot. Lett. Poland 12, 118 (2020). CrossRef M. Zervas, C. Codemard, "High Power Fiber Lasers: A Review", J. Sel. Top. Quantum Electron. 20, 1 (2014). CrossRef Coherent LMA-YDF-20/400-VIII fiber specification. DirectLink Coherent LMA-YDF-20/400-M fiber specification. DirectLink ISO 11146 norm. DirectLink